Controle da coccidiose em ovinos utilizando o toltrazuril - Rodrigues, Fernando de Souza (2018)
Coccidiosis in small ruminants is an infection caused by protozoan of genus Eimeria. Currently, at least eleven species parasite sheep, being E. ovinoidalis and E. crandallis the most pathogenic. The economic importance of coccidiosis in sheep livestock, mainly in intensive system and with high stock density, is related with losses caused by clinical and subclinical infection, causing decrease of the weight gain. Coccidiosis control can be accomplished using treatment that interrupt the life cycle of the parasite and with sanitary practices, both aiming decrease the environment contamination. Currently, coccidiosis is considering a neglected disease, however coccidia infection cause economic losses to ovine production. In this context, this thesis presents three chapters, which evaluated: (1) the efficacy, cost-benefit ratio, and economic break-even point of two different toltrazuril treatment regimens for suckling lambs naturally exposed to Eimeria spp. re-infection in a grazing system; (2) evaluated the effect of treatment with toltrazuril 5%, four and two weeks before the parturition in pregnant ewes, as well as the influence of it in the dynamics of infection of lambs naturally infected by Eimeria spp. in an extensive breeding system; (3) and evaluated the effect of toltrazuril 5% in a single dose in lambs maintained in a natural condition favorable to the development coccidiosis. Based on results, we emphasize that toltrazuril at the concentration assessed, has efficacy in lactating lambs and kept in condition to developmente coccidiosis. Treatment with toltrazuril at 14-day intervals was effective in controlling re-infection of lambs and a single dose can reduce the excretion of oocysts in lambs kept in conditions favorable to development coccidiosis. The use of toltrazuril 5% four and two weeks before the parturition reduced significantly oocyst excretion 21 days before the parturition and 14 days postpartum but did not influence the dynamics of lamb infection. E. ovinoidalis, E. crandallis, E. parva and E. ahsata were the frequently species identified causing mainly subclinical infection. Lambs kept in conditions favorable to development coccidiosis and lactating lambs treated with toltrazuril did not have a significant weight gain (p>0.05) than animals maintained naturally infected. Treatment with toltrazuril at the concentration assessed may be costly when the animals have subclinical infection, but where there are clinical cases and death, the use of this medicine may be economically viable. Economic viability of the treatment can be evaluated with the use of the economic model that aims to determine the point where the treatment becomes economically feasible. To control coccidiosis in sheep, should evaluate the specific situation of each property, the risks of developing the disease and if is necessary to use toltrazuril.